I Hate the Global Warming Factory! Caring for Tadpoles During the Climate Emergency - Hill, Cher; Whintors, Neva; Lin, Ching-Chiu (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
In this paper we share the story of our participatory action research project to create a lunchtime program to support elementary school students in building reciprocal relationships with the land, enhancing collective wellness. An emergent pond that suddenly dried up due to unseasonably warm temperatures, leaving tadpoles stranded, became the focus of much of our learning. The children worked tirelessly to restore the pond and care for the tadpoles. Through this research, we learned how impactful environmental education can be when it is guided by love (verses logic), involves thinking with (rather than thinking about) more-than-human kin, and when children actively participate in knowledge creation and mobilization through digital storytelling. Our study illustrates how action-research serves as a generative approach to participatory planetary health, inspiring both individual and collective action to address the multifaceted environmental crisis.